Kubernetes : an enterprise guide : effectively containerize applications, integrate enterprise systems, and scale applications in your enterprise /: an enterprise guide : effectively containerize applications, integrate enterprise systems, and scale applications in your enterprise. (2021) - Boorshtein, Marc; Surovich, Scott
No abstract available